Palliative neurology - Maddocks, Ian (Cambridge : Cambridge University Press, 2006)
Palliative care affirms the value of holistic support for persons facing death from advanced disease. Increasingly the approach of palliative care is seen as relevant not only to terminal cancer (its initial concern) but also to many other incurable conditions. To date, the major emphasis of specialist neurology has been on diagnosis, and the continuing long term management of the many major diseases has received far less attention. This handbook aims to provide succinct and practical advice on the management of major neurological disorders in both their supportive and terminal phases, recognizing that these conditions are increasing in prevalence in virtually every society as the proportion of elderly persons grows. It demonstrates how the discomforts encountered in dementia, stroke, Parkinson's disease, ALS, Huntington's disease, muscular dystrophies and multiple sclerosis can benefit from the same comprehensive approach to palliation as has evolved in specialist care for cancer.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Nervous system -- Diseases -- Palliative treatment